DESIGNING A COMPONENT OF INFORMATION TECHNOLOGY OF STRAIN-GAUGE EXPERIMENTAL RESEARCH - Zinchenko, V.P.; Zinchenko, N.P. (Proceedings of National Aviation University (archive), 2005)
Components (information, program, technical information) technologies of strain-gauge experimental research of models of flight vehicles in the wind tunnels, realized on the basis by means developed by authors and methods and as their suitability and efficiency for the solution of design problems is shown, are considered.